Cognitive process dimension in K-13 e-textbooks for 4th grade students - Arif Wiyat Purnanto; Putri Meinita Triana; Laili Etika Rahmawati (Intelektual Pustaka Media Utama, 2020)
Cognitive dimensions development is one of the objective of education. This research aimed to identify the structure, evaluate the focus, analyze the conformity toward the referred adoption standard, and evaluate the emphasis of thinking skill order of cognitive processes in the e-textbook for 4th grade students. Evaluation was carried out for the curriculum 2013 e-textbooks published in 2014, including theme 2, 3 and 4. Identification of cognitive process dimensions was carried out using revised Bloom’s taxonomy, while the conformity was anayzed using Alzu’bi’s preference. Statistical analysis was carried out with chi-square test. The result showed that the structure of cognitive dimensions in three examined e-textbooks were not consistent one another. Theme 2 emphasized on the high order thinking skill focused on the creating dimension. Theme 3 emphasized on the low order thinking skill focused on the understanding dimension. While theme 3 facilitated both thinking skill orders with a little tendency to the evaluating dimension. There was no conformity of the cognitive dimensions structure of the three themes toward the referred adoption standard. Statistical analysis showed that there was significant difference on the structure of cognitive dimensions between themes, and between each themes and the referred adoption standard.